The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40069-015-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Self-consolidating Concrete with Expanded Shale Aggregates: Modelling and Optimization

Abstract: This paper presents statistical models developed to study the influence of key mix design parameters on the properties of lightweight self-consolidating concrete (LWSCC) with expanded shale (ESH) aggregates. Twenty LWSCC mixtures are designed and tested, where responses (properties) are evaluated to analyze influence of mix design parameters and develop the models. Such responses included slump flow diameter, V-funnel flow time, J-ring flow diameter, J-ring height difference, L-box ratio, filling capacity, sie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 21 publications
(24 reference statements)
1
35
0
Order By: Relevance
“…The reasons for such increased interest are its unique advantages over normal weight concrete such as reduction in dead loads leading to smaller structural member as well as foundation size, ease of the shipping and transportation in case of precast structural members, and reduced overall construction cost. In addition LWC offers excellent durability in chemical and frost attack with reduced permeability (Li 2011), greater fire resistance (ACI 216.1 1997) and better thermal insulation (ACI 213 2003). The unit weight of LWC lies in the range of 1200-1800 kg/m 3 (Li 2011) while for structural LWC in general ACI Committee 213 defines the range as 1120-1920 kg/m 3 (ACI 213 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for such increased interest are its unique advantages over normal weight concrete such as reduction in dead loads leading to smaller structural member as well as foundation size, ease of the shipping and transportation in case of precast structural members, and reduced overall construction cost. In addition LWC offers excellent durability in chemical and frost attack with reduced permeability (Li 2011), greater fire resistance (ACI 216.1 1997) and better thermal insulation (ACI 213 2003). The unit weight of LWC lies in the range of 1200-1800 kg/m 3 (Li 2011) while for structural LWC in general ACI Committee 213 defines the range as 1120-1920 kg/m 3 (ACI 213 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition LWC offers excellent durability in chemical and frost attack with reduced permeability (Li 2011), greater fire resistance (ACI 216.1 1997) and better thermal insulation (ACI 213 2003). The unit weight of LWC lies in the range of 1200-1800 kg/m 3 (Li 2011) while for structural LWC in general ACI Committee 213 defines the range as 1120-1920 kg/m 3 (ACI 213 2003). In order to achieve the desired unit weight with adequate mechanical properties, careful selection and efficient utilization of lightweight filler (LWF) materials is imperative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively low-density aggregates can be obtained by substituting classical aggregates of sand and pea gravel with artificially lighter aggregates, such as expanded polystyrene beads (Chen and Liu 2004;Khedari et al 2003). Experimental works have shown that the characteristics of the aggregates are highly active in lightweight concretes, dictating the good mechanical, thermal, and acoustical performance of the final concrete (Lotfy et al 2015;de Sensale and Goncalves 2014;Chi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the effects of scorias as replacements for cement, namely with respect to the mortar toughness, cement fraction (Al-Swaidani and Aliyan 2015;Bondar 2015;Lotfy et al 2015;Ghrici et al 2007;Rabehi et al 2014), the fabrication of granulate forms for lightweight concretes (Mouli and Khelafi 2008), and thermal activation (Ezziane et al 2007). Most studies have shown that scorias are economically sound and ecologically friendly building materials (Vlček et al 2014).…”
Section: Introductionmentioning
confidence: 99%